1998
DOI: 10.1364/ao.37.001596
|View full text |Cite
|
Sign up to set email alerts
|

Laser sensing of a subsurface oceanic layer II Polarization characteristics of signals

Abstract: In Part I of this paper we calculated depth profiles and polarization characteristics of airborne lidar return signals by the Monte Carlo method. Here we calculate the polarization characteristics of lidar return signals for different types of water. We demonstrate the feasibility of polarization lidar application to the detection of underwater inhomogeneities of different origins. It is shown that simultaneous analysis of depth profiles of the lidar return signal power and signal depolarization ratio substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…Qualitatively, this experimental behavior coincided with the theoretical behavior of δ(z) reported in [6].…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Qualitatively, this experimental behavior coincided with the theoretical behavior of δ(z) reported in [6].…”
supporting
confidence: 87%
“…The qualitative functional dependence of the bias on the parameters of the lidar-sea system was simulated by the Monte Carlo method and measured experimentally in situations imitating airborne sensing. The algorithm of mathematical modeling of laser hydrooptical sensing and its accuracy were considered in detail in [6].…”
mentioning
confidence: 99%
“…For polarized light, β depends on the plane of polarization relative to ϕ. 33,34 In principle, the calculation continues until the photon passes through the plane of the receiver, where it is weighted by a factor expð− P a i l i Þ, where a i is the absorption coefficient along the i'th path segment (of length l i ). In practice, it is generally necessary to enhance the occurrence of low-probability backscattering events and compensate for this with an additional weighting factor.…”
Section: Basic Characteristicsmentioning
confidence: 99%
“…Lidar systems have been proposed as an effective tool for oceanic research as demonstrated by a variety of measurements in the upper ocean, including profiling schools of fish [ Churnside et al ., ], bathymetry [ Guenther et al ., ], and ocean surface roughness and subsurface measurements [ Bufton et al ., ; Hu et al ., ; Krekov et al ., ]. Internal waves have also been detected through the phytoplankton signatures they induce [ Churnside et al ., ].…”
Section: Introductionmentioning
confidence: 99%